4y=(y-5)-3

Simple and best practice solution for 4y=(y-5)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4y=(y-5)-3 equation:


Simplifying
4y = (y + -5) + -3

Reorder the terms:
4y = (-5 + y) + -3

Remove parenthesis around (-5 + y)
4y = -5 + y + -3

Reorder the terms:
4y = -5 + -3 + y

Combine like terms: -5 + -3 = -8
4y = -8 + y

Solving
4y = -8 + y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1y' to each side of the equation.
4y + -1y = -8 + y + -1y

Combine like terms: 4y + -1y = 3y
3y = -8 + y + -1y

Combine like terms: y + -1y = 0
3y = -8 + 0
3y = -8

Divide each side by '3'.
y = -2.666666667

Simplifying
y = -2.666666667

See similar equations:

| 3x+2(x+7)=4-3(1-2x) | | 6a-4=6a+8 | | b+3+5=0 | | -6y+12=66 | | -0.3x=42 | | g(-1)g(x)=5x^2+2x-3 | | .5(2-6x)-4(x+1.5)=-(x-3)+4 | | 3x-35=7x-3 | | 4x^2-25=12 | | -5-16=8(3y+4)-5(3y-7) | | -4+12n+2n=-4+14n | | 7+7x=-63 | | 8(4x-9)=4w(8x+2) | | 7k-5=15 | | 5b-5+2b=3b+11 | | -7(1-n)-7n=-16+3n | | 4.905*t^2+1.6*t-12=0 | | 2x+7=-17-4z | | y+10-9x=0 | | -5e+(-3)=27 | | 10x+3y(2x+5)=19 | | 38+4y-9=12y-13-2y | | X^2+30x=-224 | | m^2-4m+4m=0 | | 33=32x+4y | | 5x^2+8x+-69=0 | | -2=-5-x-5 | | 54=-28w-9 | | 9y-8y-4=6 | | 2.6=2r | | e^3x=4e^2x | | 5x+13=4x-(3x-17) |

Equations solver categories